2017
DOI: 10.1177/0363546517704835
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiology and Effect of Sliding Injuries in Major and Minor League Baseball Players

Abstract: Injuries occurring while sliding in professional baseball result in a significant amount of time out of play for these elite athletes. Injuries occurring at second base and those occurring to the hands and fingers were most prevalent and may be an appropriate target for future injury prevention programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
73
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(75 citation statements)
references
References 13 publications
2
73
0
Order By: Relevance
“…Their incidence has been found to increase significantly, and it has been reported that between 25 and 33% of all MLB pitchers have had an MUCL reconstruction surgery at some point during their baseball careers [4•, 44, 45, 48]. Research has also been conducted to further characterize other clinically relevant injuries such as abdominal oblique injuries, lumbar spine injuries, and sliding-related injuries [49][50][51].…”
Section: Epidemiologymentioning
confidence: 99%
“…Their incidence has been found to increase significantly, and it has been reported that between 25 and 33% of all MLB pitchers have had an MUCL reconstruction surgery at some point during their baseball careers [4•, 44, 45, 48]. Research has also been conducted to further characterize other clinically relevant injuries such as abdominal oblique injuries, lumbar spine injuries, and sliding-related injuries [49][50][51].…”
Section: Epidemiologymentioning
confidence: 99%
“…The HITS database has proven to be an excellent source for epidemiologic studies involving injuries in baseball, such as recent studies on abdominal oblique injuries, sliding injuries, elbow injuries, and hamstring strains. 1 , 5 , 6 , 9 …”
Section: Methodsmentioning
confidence: 99%
“…While 43.7% of these injuries were due to head-first slides and 56.3% were from feet-first slides, injury rates were not significantly different between the two approaches. 4 On the other hand, in a season-long study of 10 high school baseball and nine softball teams, Stovak et al. 5 found injury rates were significantly higher with head-first than feet-first slides in baseball players, but not softball players.…”
Section: Introductionmentioning
confidence: 98%
“…Both head-first and feet-first slides demonstrate injury risk, 1 and multiple research studies 29 have examined injuries related to sliding in baseball and softball. For instance, Dick et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation